Ocean underwater in-situ induced self-repairing agent, self-reinforced cement-based material and preparation method of self-reinforced cement-based material

By developing an in-situ induced self-repairing agent and self-reinforced cement-based material under the ocean water, and using erosion ions in seawater to activate nanomaterials, the problem of poor durability of traditional cement-based materials in marine environments is solved, the self-repair and self-enhancement of materials is achieved, and maintenance costs are reduced.

CN119797794APending Publication Date: 2025-04-11SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598793.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional cement-based materials have poor durability in marine environments and are easily damaged during long-term soaking and erosion of seawater, resulting in high cost of repairing and reinforcing coastal infrastructure.

Method used

A marine underwater in situ induced self-healing agent and self-reinforced cement-based material are developed to activate nanomaterials using erosion ions in seawater to form high-strength expanded hydration products and C-S-H gels to achieve self-repair and self-enhancement of cracks.

Benefits of technology

This material can self-start repair reaction in seawater, fill cracks, block crack expansion, achieve self-enhancement of the overall structure, reduce maintenance costs, and maintain repair effect under seawater erosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797794A_ABST
    Figure CN119797794A_ABST
Patent Text Reader

Abstract

The invention discloses an ocean underwater in-situ induced self-repairing agent, a self-reinforced cement-based material and a preparation method of the self-reinforced cement-based material. The self-repairing agent comprises an inner core formed by activated nano gamma-Al2O3 and / or SiO2 and nano CaO and / or Ca (OH) 2, and an organic-inorganic composite ion-induced targeting coating layer (OIM) formed by mixing a calcium-based water absorbing material and an organic polymer material, wherein the surface of the inner core is coated with the organic-inorganic composite ion-induced targeting coating layer (OIM); the isolation coating layer is formed by an organic polymer material which is bonded and coated on the surface of the ion-induced targeting coating layer, and the isolation coating layer is connected with the ion-induced targeting coating layer through a-COO-bond formed by dehydration condensation of-OH and-COOH. The self-repairing agent disclosed by the invention can utilize erosion ions in seawater to activate the self-reinforcing component when cracks in a cement-based material structure just start to expand, so that self-repairing and self-reinforcing of the cracks are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of marine engineering concrete, and in particular to an underwater marine in-situ induced self-repairing agent and a self-reinforced cement-based material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, the construction of large-scale inland infrastructure in my country has become increasingly complete, and the construction of regional infrastructure such as coastal docks and ocean islands has gradually been carried out on a large scale. However, in the special environment of the ocean, the durability of marine engineering concrete prepared with traditional cement-based materials is relatively poor, especially for cement concrete structures that have been underwater in seawater for a long time. They are easily damaged during long-term immersion and scouring in seawater, which leads to huge costs for the later repair, reinforcement and daily operation and maintenance of a large number of major infrastructure such as coastal docks.

[0004] Traditional measures for cement concrete repair and reinforcement in marine environments mainly include the following: First, when minor damage occurs on the concrete surface, surface repair is used to repair cracks, peeling, and damage on the concrete surface. Commonly used materials include cement mortar or polymer repair mortar. Second, when larger cracks appear in the concrete, epoxy resin, polyurethane and other materials are usually used to grout or fill the cracks inside the concrete, and then surface treatment is performed. However, the above-mentioned repair method not only has the problem of unsightly concrete surface after repair, but also the bonding force between the newly repaired area and the original matrix is ​​weak after repair, and it is very easy to peel off again under the action of seawater erosion. In addition, a lot of manpower and material resources are required for repair and reinforcement, and the maintenance cost is high. Therefore, it is necessary to study cement-based materials that can self-repair and self-reinforce under seawater erosion. Summary of the invention

[0005] In view of this, the present invention provides an underwater in-situ induced self-repairing agent and a self-reinforced cement-based material and a preparation method thereof, which can activate the self-reinforcement component by utilizing the corrosive ions in seawater when the crack just begins to expand, thereby achieving self-repair and self-reinforcement of the crack. Specifically, the present invention discloses the technical solution as shown below.

[0006] First, the present invention provides an underwater marine in-situ induced self-repairing agent, which includes activated nano γ-Al 2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2The formed inner core comprises an organic-inorganic composite ion-induced targeting coating layer (OIM) composed of a mixture of a calcium-based water-absorbing material and an organic polymer material coated on the surface of the inner core, and an isolation coating layer formed by an organic polymer material bonded and coated on the surface of the ion-induced targeting coating layer, wherein the isolation coating layer and the ion-induced targeting coating layer are connected via a -COO- bond formed by dehydration condensation of -OH and -COOH.

[0007] Furthermore, the activated nano γ-Al 2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2 The mass ratio is 0.5~1.5:0.5~1.5.

[0008] Furthermore, the mass ratio of the calcium-based water-absorbing material to the organic polymer material is 0.5-1.5:0.5-1.5.

[0009] Furthermore, the calcium-based water-absorbing material includes at least one of calcium-based bentonite, calcium-based montmorillonite, and the like.

[0010] Furthermore, in the induced targeting coating layer, the organic polymer material includes at least one of polyvinyl alcohol rubber powder (PVA), ethylene-vinyl acetate rubber powder (EVA), and the like.

[0011] Furthermore, in the isolation coating layer, the organic polymer material includes at least one of vinyl acetate-ethylene copolymer (VAE), acrylic emulsion (PA), and the like.

[0012] Secondly, the present invention discloses a method for preparing the underwater marine in-situ induced self-repairing agent, comprising the following steps:

[0013] (1) using acid solution to treat the nano γ-Al 2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2 The activation treatment is carried out, and after completion, it is washed, dried, ground and sieved to obtain activated nanomaterials.

[0014] (2) The calcium-based water-absorbing material and the polymer powder material are mixed and spread on the tray of a constant temperature and humidity oscillator to form an organic-inorganic composite ion-induced targeted coating material powder layer. After the humidity reaches a set value, the activated nanomaterial is spread on the powder layer, and then the powder layer is oscillated under heating conditions. After completion, it is dried to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by a targeted coating layer coated on the core.

[0015] (3) Spreading the single-layer core-shell structure particles into the emulsion layer formed by the flat organic polymer material, and then shaking the emulsion layer under heating conditions. After completion, the particles are separated and dried to obtain a double-layer coated core-shell crack repair agent.

[0016] Furthermore, in step (1), the acid solution includes at least one of nitric acid, sulfuric acid, etc. Optionally, the concentration of the acid solution is 9 to 18.5 mol / L. The acid solution treatment can effectively increase the 2 O 3 and / or SiO 2 More hydrophilic hydroxyl reaction active sites are exposed on the surface, making it easier for the calcium-based water-absorbing material to capture and coat the surface.

[0017] Furthermore, in step (1), the activation treatment time is 8 to 20 hours. The acid solution is added to 2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2 Just submerge.

[0018] Furthermore, in step (1), clean water is used for washing to remove the nano-γ-Al 2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2 Acid residue on the surface.

[0019] Furthermore, in step (2), the ratio of the activated nanomaterial to the organic-inorganic composite ion-induced targeted coating material powder layer is 3 to 15 parts by weight: 15 to 35 parts by weight. Optionally, the thickness of the organic-inorganic composite ion-induced targeted coating material powder layer is 0.2 to 0.6 mm. The fineness of the organic-inorganic composite ion-induced targeted coating material is 1000 to 1500 mesh.

[0020] Furthermore, in step (2), the humidity is 60-70%.

[0021] Furthermore, in step (2), the heating temperature is 60 to 100° C., the frequency of the oscillation treatment is 260 to 400 rpm, and the time is 0.5 to 2.5 hours.

[0022] Furthermore, in step (2), the drying temperature is 30 to 60° C., and the drying time is 8 to 16 hours.

[0023] Furthermore, in step (3), the mass ratio of the single-coated core-shell structure particles to the organic polymer material emulsion layer is 18 to 50 parts by weight: 10 to 50 parts by weight. Optionally, the mass concentration of the organic polymer emulsion is 30 to 60%. The thickness of the organic polymer material emulsion layer is 0.2 to 0.6 mm.

[0024] Furthermore, in step (3), the heating temperature is 30-50°C, the frequency of the oscillation treatment is 150-200rpm, and the time is 0.2-2h. The organic polymer emulsion of this step can form a dense, impermeable, and difficult to break isolation coating layer in the ion-induced targeted coating layer, which prevents the above-mentioned single-coating core-shell structure particles from participating in the reaction during the cement mixing process and losing the repair and enhancement ability, and enables the repair agent of the present invention to be dispersed more evenly in the cement slurry and reduce agglomeration. In addition, the surface of the isolation coating layer is exposed acetate (VAE emulsion coating) / carboxyl (PA emulsion coating) can combine with Ca ions generated during cement hydration to form calcium acetate / calcium acrylate, so as to achieve the purpose of close bonding with the cement matrix, so that the coating layer of the cement matrix can be torn at the first time during the stress cracking process.

[0025] Furthermore, in step (3), the drying temperature is 50 to 80° C., and the drying time is 1 to 6 hours.

[0026] Again, the present invention discloses an underwater marine in-situ induced self-reinforced cement-based material, the raw materials of which include the following components: 70 to 95 parts by weight of silicate cement and 5 to 35 parts by weight of the above-mentioned crack repairing agent of the present invention.

[0027] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0028] The present invention first uses highly active nanomaterials as the basic component, and coats the surface of the material with an ion-induced targeted coating layer formed by an organic-inorganic composite ion-induced targeted coating material, and then performs a hydrophilic rigid coating to form the above-mentioned isolation coating layer, thereby obtaining a double-layer coated core-shell marine underwater in-situ induced self-repairing agent, which not only allows the repair agent to remain as stable as possible during the manufacturing process of the cement-based material structure, but also starts to react under the action of the generated cracks, thereby avoiding premature participation in the reaction and causing the repair ability of the repair agent to decrease or even fail. When a building structure prepared with cement-based materials containing the above-mentioned repair agent of the present invention is in service in seawater, the tensile stress caused by the cracks generated therein can easily tear the isolation coating layer on the surface of the repair agent particles, thereby exposing the internal ion-induced targeted coating layer to the cracks. At this time, the ion-induced targeted coating layer uses its own high water absorption characteristics to quickly induce seawater to enter and diffuse, and then reacts with the nano γ-Al in the repair agent.2 O 3 and / or SiO 2 , nano-CaO and / or Ca(OH) 2 Full contact, using the characteristics of seawater rich in sulfate ions to activate the nano γ-Al 2 O 3 , which can react with the sulfate to generate a high-strength expansive hydration product, ettringite AFt (2A1 3+ +3SO 4 2- +6Ca(OH) 2 +26H 2 O→3CaO·Al 2 O 3 ·3CaSO 4 ·32H 2 O, i.e. AFt), and the nano-SiO 2 It can react with calcium ions produced by cement hydration to form hydration product CSH gel (nCa(OH) 2 +SiO 2 +mH 2 O→nCaO·SiO 2 ·(n+m)H 2 O, namely CSH). The above-mentioned gelled products can be accumulated at the cracks, thereby quickly filling the cracks, blocking the crack extension direction, and preventing microcracks from expanding into large cracks. At the same time, the formation of the above-mentioned gelled products also realizes the self-reinforcement of the overall structure, and the entire enhanced repair process does not require external intervention. In addition, since the organic-inorganic composite ion-induced targeted coating layer (OIM) of the present invention is based on a flexible network formed after the organic polymer material is emulsified in water, it is complexed with the calcium-based water-absorbing material to form a relatively loose and exquisite structure, and the calcium-based water-absorbing material is extremely easy to break and disintegrate in the alkaline environment formed by the contact between the activated nanomaterial kernel and seawater, which is convenient for seawater to enter the kernel for hydration reaction. However, since the flexible network can stably exist in the process of hydration reaction between ions in seawater and the activated nanomaterial kernel, it can provide a growth site for the hydration product generated by the hydration reaction, and can be used as a "cage" to physically lock the hydration product generated in the early stage of the above-mentioned hydration reaction, which helps to prevent the formed hydration product from being washed away by seawater, and further improve the repair and enhancement effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1 This is a sample picture of the in-situ induced self-healing agent prepared in Example 1 below.

[0031] Figure 2 This is a compressive strength test diagram in the following Example 1.

[0032] Figure 3 This is a bonding strength test diagram in the following Example 1.

[0033] Figure 4 The planed surface image (left image) and the SEM image (right image) of the local area of ​​the self-reinforced cement-based material containing the in-situ induced self-healing agent described in the following Example 1 after splitting. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0035] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.

[0036] In the following examples, the component contents of each 1000 g of the artificial simulated seawater are shown in the following table:

[0037] NaCl <![CDATA[CaCl 2 ]]> KCl <![CDATA[MgCl 2 ]]> <![CDATA[MgSO 4 ]]> Deionized water 28.208g 1.253g 0.722g 1.101g 3.312g 965.404g

[0038] Example 1

[0039] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0040] (1) Nano-γ-Al 2 O 3 The mixture was mixed with nano-CaO in a mass ratio of 1:1 and stirred evenly, and then placed in 15 mol / L nitric acid, stirred evenly and allowed to stand for 12 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove residual acid. After drying at 50 degrees Celsius for 48 hours, it was ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0041] (2) The calcium-based water-absorbing material (calcium-based bentonite powder) and the organic polymer material (polyvinyl alcohol powder) are mixed in a mass ratio of 1:1 to obtain an organic-inorganic composite ion-induced targeted coating material powder (fineness of 1000 mesh). The activated nanomaterial and targeted coating material powder of this embodiment are weighed in a ratio of 10 parts by weight: 25 parts by weight. Then the targeted coating material powder is spread on a constant temperature horizontal oscillator (the thickness of the spread is 0.5 mm) to form a coating powder layer, and the temperature in the oscillator is set to be kept at a constant temperature of 80°C. After the humidity in the oscillator reaches 60%, the activated nanomaterial is spread on the above-mentioned coating powder layer and vibrated at a vibration frequency of 300 rpm for 1 hour. After completion, vacuum drying is performed at 40°C for 12 hours to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core.

[0042] (3) Pour a 40% mass concentration of vinyl acetate-ethylene copolymer emulsion (VAE) into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.5 mm, then add the core-shell structure particles to the emulsion according to a mass ratio of the single-coating core-shell structure particles to the emulsion of 30:20, set the temperature in the oscillator to be maintained at a constant temperature of 45°C, and then vibrate at a vibration frequency of 150 rpm for 2 hours. After completion, the obtained particles are vacuum dried at 65°C for 3 hours to obtain a self-healing agent (such as Figure 1 shown).

[0043] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 80 parts by weight of silicate cement, 20 parts by weight of the self-healing agent prepared in this embodiment, and 300 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0044] Performance test: (1) According to the "Standard for Test Methods for Self-Healing Performance of Cement Concrete" (T / CECS 913-2021), the self-repair rate of cracks in the cement-based material prepared in this embodiment is tested to measure the self-repair ability of cracks. (2) Referring to the "Standard for Test Methods for Basic Performance of Building Mortar" (JGJ T70-09), the test blocks made of the cement-based material of this embodiment are cured to an age of 28 days, and then prestressed to the test blocks to artificially preset cracks. The initial width of the cracks is 350 to 450 μm. The obtained test blocks are then immersed in artificial simulated seawater for 56 days, and a part of the test blocks are taken to test the compressive strength retention rate of the test blocks according to the "Test Methods for Cement Resistance to Seawater Erosion" (GBT 38140-2019). Figure 2 As shown. Another part of the test blocks were subjected to pull-out bonding tests at both ends of the crack to test the bonding strength at the crack, as shown Figure 3 The test results of the above indicators are shown in the following table. Figure 4 The planed surface image (left) and the SEM image of the local area (right) of the test block after splitting after immersion for 56 days show that the self-healing agent has started to play a role and repaired the cracks.

[0045] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 98.5% 97.1% 1.53MPa

[0046] Example 2

[0047] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0048] (1) Nano-γ-Al 2 O 3 and nano-Ca(OH) 2 The mixture was mixed in a mass ratio of 0.5:1.5 and stirred evenly, and then the obtained mixture was placed in 9 mol / L nitric acid, stirred evenly, and then allowed to stand for 20 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove residual acid solution. After drying at 50 degrees Celsius for 48 hours, it was ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0049] (2) The calcium-based water-absorbing material (calcium-based bentonite powder) and the organic polymer material (ethylene-vinyl acetate rubber powder) are mixed uniformly at a mass ratio of 0.5:1.5 to obtain an organic-inorganic composite ion-induced targeted coating material powder (fineness of 1500 mesh). The activated nanomaterial and targeted coating material powder of this embodiment are weighed in a ratio of 3 parts by weight: 15 parts by weight. Then the targeted coating material powder is spread on a constant temperature horizontal oscillator (the thickness of the spread is 0.6 mm) to form a coating powder layer. The temperature in the oscillator is set to be kept at a constant temperature of 100°C. After the humidity in the oscillator reaches 65%, the activated nanomaterial is spread on the above-mentioned coating powder layer and vibrated at a vibration frequency of 260rpm for 2.5 hours. After completion, it is vacuum dried at 30°C for 16 hours to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core.

[0050] (3) Pour a 30% mass concentration of vinyl acetate-ethylene copolymer emulsion (VAE) into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.2 mm, then add the core-shell structure particles to the emulsion according to a mass ratio of the single-coating core-shell structure particles to the emulsion of 18:10, set the temperature in the oscillator to be kept at a constant temperature of 50° C., and then vibrate at a vibration frequency of 180 rpm for 1.5 hours. After completion, the obtained particles are vacuum dried at 50° C. for 6 hours to obtain a self-healing agent.

[0051] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 70 parts by weight of silicate cement, 35 parts by weight of the self-healing agent prepared in this embodiment, and 315 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0052] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0053] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 90.3% 89.8% 1.03MPa

[0054] Example 3

[0055] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0056] (1) Nano-γ-Al 2 O 3 and nano-γ-SiO 2 (The mass ratio of the two is 3:1), nano-Ca(OH) 2 The mixture was mixed in a mass ratio of 1.5:0.5 and stirred evenly, and then the obtained mixture was placed in 18.5 mol / L sulfuric acid, stirred evenly, and then allowed to stand for 8 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove residual acid. After drying at 50 degrees Celsius for 48 hours, it was ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0057] (2) The calcium-based water-absorbing material (calcium-based montmorillonite powder) and the organic polymer material (polyvinyl alcohol powder) are mixed uniformly in a mass ratio of 1.5:0.5 to obtain an organic-inorganic composite ion-induced targeted coating material powder (fineness of 1200 mesh). The activated nanomaterial and targeted coating material powder of this embodiment are weighed in a ratio of 15 parts by weight: 35 parts by weight. Then the targeted coating material powder is spread on a constant temperature horizontal oscillator (the thickness of the spread is 0.2 mm) to form a coating powder layer, and the temperature in the oscillator is set to be kept at a constant temperature of 60°C. After the humidity in the oscillator reaches 70%, the activated nanomaterial is spread on the above-mentioned coating powder layer and vibrated at a vibration frequency of 400 rpm for 0.5 hours. After completion, it is vacuum dried at 60°C for 8 hours to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core.

[0058] (3) Pour an acrylic emulsion (PA) with a mass concentration of 60% into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.6 mm, then add the core-shell structure particles into the emulsion according to a mass ratio of the single-coating core-shell structure particles to the emulsion of 50:50, set the temperature in the oscillator to be kept at a constant temperature of 30° C., and then vibrate at a vibration frequency of 200 rpm for 0.2 hours. After completion, the obtained particles are vacuum dried at 80° C. for 1 hour to obtain a self-healing agent.

[0059] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 95 parts by weight of silicate cement, 5 parts by weight of the self-healing agent prepared in this embodiment, and 300 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0060] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0061] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 95.5% 93.2% 1.27MPa

[0062] Example 4

[0063] An underwater in-situ induced self-reinforced cement-based material comprises the following components: 80 parts by weight of silicate cement and 300 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0064] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0065] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 5.3% 2.8% 0.06MPa

[0066] Example 5

[0067] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0068] (1) Nano-γ-Al 2 O 3 and nano-Ca(OH) 2 The mixture is mixed in a mass ratio of 0.5:1.5 and stirred evenly to obtain a nano material.

[0069] (2) The calcium-based water-absorbing material (calcium-based bentonite powder) and the organic polymer material (ethylene-vinyl acetate rubber powder) are mixed uniformly at a mass ratio of 0.5:1.5 to obtain an organic-inorganic composite ion-induced targeted coating material powder (fineness of 1500 mesh). The nanomaterial and targeted coating material powder of this embodiment are weighed in a ratio of 3 parts by weight: 15 parts by weight. Then the targeted coating material powder is spread on a constant temperature horizontal oscillator (the thickness of the spread is 0.6 mm) to form a coating powder layer. The temperature in the oscillator is set to be maintained at a constant temperature of 100°C. After the humidity in the oscillator reaches 65%, the nanomaterial is spread on the above-mentioned coating powder layer and vibrated at a vibration frequency of 260rpm for 2.5 hours. After completion, it is vacuum dried at 30°C for 16 hours to obtain a core formed by the nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core.

[0070] (3) Pour a 30% mass concentration of vinyl acetate-ethylene copolymer emulsion (VAE) into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.2 mm, then add the core-shell structure particles to the emulsion according to a mass ratio of the single-coating core-shell structure particles to the emulsion of 18:10, set the temperature in the oscillator to be kept at a constant temperature of 50° C., and then vibrate at a vibration frequency of 180 rpm for 1.5 hours. After completion, the obtained particles are vacuum dried at 50° C. for 6 hours to obtain a self-healing agent.

[0071] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 70 parts by weight of silicate cement, 35 parts by weight of the self-healing agent prepared in this embodiment, and 315 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0072] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0073] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 74.3% 66.2% 0.62MPa

[0074] Example 6

[0075] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0076] (1) Nano-γ-Al 2 O 3 and nano-γ-SiO 2 (The mass ratio of the two is 3:1), nano-Ca(OH) 2The mixture was mixed in a mass ratio of 1.5:0.5 and stirred evenly, and then the obtained mixture was placed in 18.5 mol / L sulfuric acid, stirred evenly, and then allowed to stand for 8 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove the residual acid solution, dried at 50 degrees Celsius for 48 hours, and then ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0077] (2) The calcium-based water-absorbing material (calcium-based montmorillonite powder) and the organic polymer material (polyvinyl alcohol powder) are mixed uniformly in a mass ratio of 1.5:0.5 to obtain an organic-inorganic composite ion-induced targeted coating material powder (fineness of 1200 mesh). The activated nanomaterial and targeted coating material powder of this embodiment are weighed in a ratio of 15 parts by weight: 35 parts by weight. Then the targeted coating material powder is spread on a constant temperature horizontal oscillator (the thickness of the spread is 0.2 mm) to form a coating powder layer, and the temperature in the oscillator is set to be kept at a constant temperature of 60°C. After the humidity in the oscillator reaches 70%, the activated nanomaterial is spread on the above-mentioned coating powder layer and vibrated at a vibration frequency of 400 rpm for 0.5 hours. After completion, it is vacuum dried at 60°C for 8 hours to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core, that is, a self-healing agent.

[0078] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 95 parts by weight of silicate cement, 5 parts by weight of the self-healing agent prepared in this embodiment, and 300 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0079] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0080] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 23.7% 19.4% 0.11MPa

[0081] Example 7

[0082] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0083] (1) Nano-γ-Al 2 O 3 and nano-Ca(OH) 2 The mixture was mixed in a mass ratio of 0.5:1.5 and stirred evenly, and then the obtained mixture was placed in 9 mol / L nitric acid, stirred evenly, and then allowed to stand for 20 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove residual acid solution. After drying at 50 degrees Celsius for 48 hours, it was ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0084] (2) Pour a 30% mass concentration of vinyl acetate-ethylene copolymer emulsion (VAE) into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.2 mm, then add the activated nanomaterial to the emulsion at a mass ratio of 18:10, set the temperature in the oscillator to be kept at a constant temperature of 50° C., and then vibrate at a vibration frequency of 180 rpm for 1.5 hours. After completion, the obtained particles are vacuum dried at 50° C. for 6 hours to obtain a self-healing agent.

[0085] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 70 parts by weight of silicate cement, 35 parts by weight of the self-healing agent prepared in this embodiment, and 315 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0086] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0087]

[0088]

[0089] Example 8

[0090] 1. A method for preparing an underwater in-situ induced self-repairing agent, comprising the following steps:

[0091] (1) Nano-γ-Al 2 O 3 and nano-γ-SiO 2 (The mass ratio of the two is 3:1), nano-Ca(OH) 2 The mixture was mixed in a mass ratio of 1.5:0.5 and stirred evenly, and then the obtained mixture was placed in 18.5 mol / L sulfuric acid, stirred evenly, and then allowed to stand for 8 hours for activation treatment. After completion, the mixture was filtered out and washed with clean water to remove residual acid. After drying at 50 degrees Celsius for 48 hours, it was ground through a 1500 mesh sieve to obtain an activated nanomaterial.

[0092] (2) Weigh the activated nanomaterial and targeted coating material powder (calcium-based montmorillonite powder with a fineness of 1200) of the present embodiment in a ratio of 15 parts by weight to 35 parts by weight. Then spread the targeted coating material powder on a constant temperature horizontal oscillator (the paving thickness is 0.2 mm) to form a coating powder layer, and set the temperature in the oscillator to maintain a constant temperature of 60°C. After the humidity in the oscillator reaches 70%, spread the activated nanomaterial on the above-mentioned coating powder layer and vibrate it at a vibration frequency of 400 rpm for 0.5 hours. After completion, vacuum dry it at 60°C for 8 hours to obtain a core formed by the activated nanomaterial and a single-coating core-shell structure particle formed by the targeted coating layer coated on the core.

[0093] (3) Pour a 30% mass concentration of vinyl acetate-ethylene copolymer emulsion (VAE) into a tray of a constant temperature oscillator to form an emulsion layer with a thickness of 0.2 mm, then add the core-shell structure particles to the emulsion according to a mass ratio of the single-coating core-shell structure particles to the emulsion of 18:10, set the temperature in the oscillator to be kept at a constant temperature of 50° C., and then vibrate at a vibration frequency of 180 rpm for 1.5 hours. After completion, the obtained particles are vacuum dried at 50° C. for 6 hours to obtain a self-healing agent.

[0094] 2. A marine underwater in-situ induced self-reinforced cement-based material, comprising the following components: 95 parts by weight of silicate cement, 5 parts by weight of the self-healing agent prepared in this embodiment, and 300 parts by weight of standard sand. The above components are mixed and stirred evenly to obtain the cement-based material.

[0095] Performance test: The same method as in Example 1 above was used to test the crack self-repair rate, compressive strength retention rate and bonding strength of the cement-based material prepared in this embodiment. The test results of each index are shown in the following table.

[0096] Test indicators Crack self-repair rate Compressive strength retention rate Bond Strength Test Results 76.8% 52.1% 0.82MPa

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A marine underwater in-situ induced self-repairing agent, characterized in that: include: Activate the inner core formed by nano-γ-Al2O3 and / or SiO2, nano-CaO and / or Ca(OH)2; An organic-inorganic composite ion-induced targeting coating layer composed of a mixture of a calcium-based water-absorbing material and an organic polymer material coated on the surface of the core; And, an isolation coating layer formed by an organic polymer material coated on the surface of the ion-induced targeting coating layer is bonded, and the isolation coating layer is connected to the ion-induced targeting coating layer through a -COO- bond formed by dehydration condensation of -OH and -COOH.

2. The marine underwater in-situ induced self-repairing agent according to claim 1, characterized in that: The mass ratio of the activated nano-γ-Al2O3 and / or SiO2 to nano-CaO and / or Ca(OH)2 is 0.5-1.5:0.5-1.

5.

3. The marine underwater in-situ induced self-repairing agent according to claim 1, characterized in that: The mass ratio of the calcium-based water-absorbing material to the organic polymer material is 0.5-1.5:0.5-1.5; Optionally, the calcium-based water-absorbing material includes at least one of calcium-based bentonite and calcium-based montmorillonite; Optionally, in the induced targeting coating layer, the organic polymer material includes at least one of polyvinyl alcohol rubber powder and ethylene-vinyl acetate rubber powder; Optionally, in the isolation coating layer, the organic polymer material includes at least one of vinyl acetate-ethylene copolymer and acrylic emulsion.

4. The method for preparing the underwater in-situ induced self-repairing agent according to any one of claims 1 to 3, characterized in that: The steps include: (1) activating the nano-γ-Al2O3 and / or SiO2, nano-CaO and / or Ca(OH)2 with an acid solution, washing, drying and grinding to obtain activated nano-materials; (2) mixing the calcium-based water-absorbing material and the polymer powder material and spreading them on a tray of a constant temperature and humidity oscillator to form an organic-inorganic composite ion-induced targeted coating material powder layer, and spreading the activated nanomaterial on the powder layer after the humidity reaches a set value, and then oscillating the powder layer under heating conditions, and drying after completion to obtain a core formed by the activated nanomaterial and a core-shell structure formed by the targeted coating layer coated on the core; (3) spreading the single-coated core-shell structure particles into the emulsion layer formed by the flat organic polymer material, and then oscillating the emulsion layer under heating conditions; after completion, separating the particles and drying them to obtain the self-healing agent.

5. The method for preparing the underwater in-situ induced self-repairing agent according to claim 4, characterized in that: In step (1), the acid solution includes at least one of nitric acid and sulfuric acid; Optionally, in step (1), the concentration of the acid solution is 9 to 18.5 mol / L; Optionally, in step (1), the activation treatment time is 8 to 20 hours; Optionally, in step (1), clean water is used for washing.

6. The method for preparing the underwater in-situ induced self-repairing agent according to claim 4, characterized in that: In step (2), the ratio of the activated nanomaterial to the organic-inorganic composite ion-induced targeted coating material powder layer is 3 to 15 parts by weight: 15 to 35 parts by weight; Optionally, in step (2), the thickness of the organic-inorganic composite ion-induced targeted coating material powder layer is 0.2 to 0.6 mm; Optionally, in step (2), the fineness of the organic-inorganic composite ion-induced targeted coating material powder layer is 600-800 mesh; Optionally, in step (2), the humidity is 60-70%; Optionally, in step (2), the heating temperature is 60 to 100° C., the frequency of the oscillation treatment is 260 to 400 rpm, and the time is 0.5 to 2.5 hours.

7. The method for preparing the underwater in-situ induced self-repairing agent according to any one of claims 4 to 6, characterized in that: In step (3), the mass ratio of the single-coating core-shell structure particles to the emulsion layer of the organic polymer material is 18 to 50 parts by weight: 10 to 50 parts by weight.

8. The method for preparing the underwater in-situ induced self-repairing agent according to any one of claims 4 to 6, characterized in that: In step (3), the mass concentration of the organic polymer emulsion is 30-60%; Optionally, in step (3), the thickness of the emulsion layer of the organic polymer material is 0.2 to 0.6 mm.

9. The method for preparing the underwater in-situ induced self-repairing agent according to any one of claims 4 to 6, characterized in that: In step (3), the heating temperature is 30-50° C., the frequency of the shaking treatment is 150-200 rpm, and the time is 0.2-2 h; Optionally, in step (3), the drying temperature is 50 to 80° C. and the drying time is 1 to 6 hours.

10. An underwater in-situ induced self-reinforced cement-based material, characterized in that: The raw materials include the following components: 70 to 95 parts by weight of silicate cement, and 5 to 35 parts by weight of the marine underwater in-situ induced self-repairing agent described in any one of claims 1 to 3 or the marine underwater in-situ induced self-repairing agent obtained by the preparation method described in any one of claims 4 to 9.